Knowledge, Attitudes, and Behaviours of New Zealand Physiotherapists to Sports-related Concussion - Reid, D; Hume, P; Whatman, C; Theadom, A; Walters, S; Hardacker, N; Fulcher, M (New Zealand Society of Physiotherapists Inc, 2020)
Sports-related concussion (SRC) is a risk across all sports. New Zealand physiotherapists are more frequently in attendance at sporting events than medical doctors. The aim of this study was to determine the knowledge, attitudes, and behaviours of physiotherapists potentially working with SRC, using a 35-item, multi-choice questionnaire. The survey was completed by 122 physiotherapists (response rate 10%). Physiotherapists were knowledgeable regarding SRC and showed positive attitudes towards correct management of the injury. Of the respondents, 98% recognised the key signs and symptoms of SRC, and 88% would refer to a medical practitioner for further assessment of SRC. Physiotherapists indicated a strong desire to be more involved in sideline management and testing, and would like to see a more multidisciplinary approach to return-to-play decision-making after SRC. Given that the knowledge, attitudes, and behaviours of New Zealand physiotherapists to SRC were very good, it is suggested that the processes in New Zealand be reviewed to enable physiotherapists to be more involved in the assessment and management of concussion.
Keywords: Concussion; Sports; Physiotherapy